A novel heat transfer modeling methodology for regenerative cooling in liquid propellant rocket engines - T. Gândara; V. Costa; J. Dias (Case Studies in Thermal Engineering)
Liquid propellant rocket engines operate at extremely high temperatures and commonly rely on regenerative cooling to protect chamber walls and maintain structural integrity. Accurate thermal modeling of these systems remains challenging due to the complex heat transfer phenomena, reliance on assumptions or empirical correlations, and the frequent use of computationally intensive CFD tools. This work introduces a custom numerical tool that predicts wall temperature and heat flux distributions using only the thermophysical properties of the combustion gases and coolant, without assuming heat transfer coefficients, temperature profiles, or using prior experimental data. The proposed methodology is an iteration-based one-dimensional model that solves coupled heat transfer equations between the hot gas, chamber wall, and coolant along the engine length. Its performance and accuracy have been validated for small engines through comparison with experimental data, other custom tools, and commercial CFD software. The model consistently predicts wall temperatures, heat fluxes, and pressure drop in sub-minute computation times, demonstrating its effectiveness for evaluating engine designs in early development stages. A representative case involving an additively manufactured small rocket engine illustrates the tool's practical value, showing how it can quickly identify thermal issues, support design trade-offs, and accelerate the development of regeneratively cooled rocket engines.